RISK PERCEPTIONS AND BRAND EXTENSION SUCCESS - (:unkn) unknown (UNIV ZAGREB, FAC TEXTILE TECH, 2010)
This research examines the role of risk perceptions on the success likelihood of brand extensions. Prior research focuses on two main factors as driving brand extension success: brand loyalty and perceived fit between the brand and the extension product. However, the role of purchasing risk perceptions (physical, financial, psychological, etc.) in driving brand extension success has not been discussed adequately in the literature. The study posits that (1) risk perceptions explain substantial incremental variance (in addition to those explained by brand loyalty and perceived fit of the extension) in consumers' willingness to purchase (WTP) measures and (2) risk perceptions also moderate the effects of brand loyalty and perceived fit on WTP. These suggestions were tested separately for childrens' products and parents' products. The results suggest that the effects of perceived fit on WTP are higher in high risk situations than those in low risk situations.
Keywords: risk perceptions; brand extension; brand loyalty; perceived fit; willingness to purchase; PERCEIVED RISK